Bone health in adolescents with idiopathic scoliosis: a comparison with age- and sex-matched controls. (February 2020) - Diarbakerli, Elias; Savvides, Panayiotis; Wihlborg, Axel; Abbott, Allan; Bergström, Ingrid; Gerdhem, Paul
Abstract : Aims: Idiopathic scoliosis is the most common spinal deformity in adolescents and children. The aetiology of the disease remains unknown. Previous studies have shown a lower bone mineral density in individuals with idiopathic scoliosis, which may contribute to the causation. The aim of the present study was to compare bone health in adolescents with idiopathic scoliosis with controls. Methods: We included 78 adolescents with idiopathic scoliosis (57 female patients) at a mean age of 13.7 years (8.5 to 19.6) and 52 age- and sex-matched healthy controls (39 female patients) at a mean age of 13.8 years (9.1 to 17.6). Mean skeletal age, estimated according to the Tanner-Whitehouse 3 system (TW3), was 13.4 years (7.4 to 17.8) for those with idiopathic scoliosis, and 13.1 years (7.4 to 16.5) for the controls. Mean Cobb angle for those with idiopathic scoliosis was 29° (SD 11°). All individuals were scanned with dual energy x-ray absorptiometry (DXA) and peripheral quantitative CT (pQCT) of the left radius and tibia to assess bone density. Statistical analyses were performed with independent-samples t -test, the Mann-Whitney U test, and the chi-squared test. Results: Compared with controls, adolescents with idiopathic scoliosis had mean lower DXA values in the left femoral neck (0.94 g/cm 2 (SD 0.14) vs 1.00 g/cm 2 (SD 0.15)), left total hip (0.94 g/cm 2 (SD 0.14) vs 1.01 g/cm 2 (SD 0.17)), L1 to L4 (0.99 g/cm 2 (SD 0.15) vs 1.06 g/cm 2 (SD 0.17)) and distal radius (0.35 g/cm 2 (SD 0.07) vs 0.39 g/cm 2 (SD 0.08; all p ≤ 0.024), but not in the mid-radius (0.72 g/cm 2 vs 0.74 g/cm 2 ; p = 0.198, independent t -test) and total body less head (1, 559 g (SD 380) vs 1, 649 g (SD 492; p = 0.0.247, independent t -test). Compared with controls, adolescents with idiopathic scoliosis had lower trabecular volume bone mineral density (BMD) on pQCT in the distal radius (184.7 mg/cm 3 (SD 40.0) vs 201.7 mg/cm 3 (SD 46.8); p = 0.029), but not in other parts of the radius or the tibia (p ≥ 0.062, Mann-Whitney U test). Conclusion: In the present study, idiopathic scoliosis patients seemed to have lower BMD at central skeletal sites and less evident differences at peripheral skeletal sites when compared with controls. Cite this article: Bone Joint J 2020;102-B(2):268–272